Implementation of Six Sigma to Reduce Defects In Batik Cap Products To Maximize Production Capacity : Case Study: PT. Batik Banten Mukarnas - Dedy Khaerudin; Ganjar Sidik Gandara; Budiharjo Budiharjo; Irma Nurmala Dewi (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
Batik Banten Mukarnas is a company that produces stamped batik designs with various patterns and varieties of batik. Problems frequently arise in the company due to increased stamped batik production capacity to meet the demand for stamped batik design products, which continues to rise from stamped batik suppliers. Another impact of growing demand capacity is the high number of defects in stamped batik cloth products, because overall, the company's management, including human resources, tools, and methods, is not prepared for the increase in production capacity to meet the surge in consumer demand, resulting in an impact on the quality of the products produced—consequently, the organization endeavors to regulate the quality of stamped batik cloth at PT. Batik Banten Mukarnas establishes objectives that employ Six Sigma with the DMAIC method (Define, Measure, Analyze, Improve, and Control) in the production of batik stamp designs to meet production objectives. The results of the data processing that has been done obtained a sigma value before improvement for 3 CTQ of 3.54. After improvement, the sigma value increased to 3.86. While for the sigma value before improvement for 1 CTQ of 3.04, the sigma value increased to 3.42 after improvement. The factors contributing to defective products, as illustrated by the fishbone diagram, include methods, personnel, materials, machinery, and environmental conditions. The division leader consistently oversees and regulates operations, enhances the number of brushes, and trains operators to ensure proficient adherence to standard operating procedures (SOP).